KONTRAK PEMBELAJARAN: REFLEKSI TERHADAP KISAH NABI MUSA DAN NABI KHIDIR STUDI SURAH AL KAHFI - Peza Verlita; Fadillah Rahma Sari, Abdul Lathif, Gusmaneli (CV. ADIBA AISHA AMIRA, 2024)
This study explores the reflections on the stories of Prophet Musa (Moses) and Prophet Khidir as presented in Surah Al-Kahfi of the Quran. The contract of learning (kontrak pembelajaran) serves as the framework for examining the valuable lessons and insights derived from these narratives. The analysis delves into the profound teachings embedded in the stories, offering a deeper understanding of moral, spiritual, and practical implications. Through a systematic study of Surah Al-Kahfi, this research aims to highlight the relevance and applicability of the lessons learned from the experiences of Prophet Musa and Prophet Khidir in contemporary contexts.